치자 추출물의 지방대사조절을 통한 비알콜성 지방간 유도 인슐린저항성 개선 효과 - 서일복(Il-bok Seo); 안상현(Sang Hyun Ahn); 정한솔(Han Sol Jeong); 김기봉(Ki Bong Kim) (동의생리병리학회지, 2019)
Gardenia jasminoides is an herbal medicine that treats obesity and dampness-phlegm. This study aimed to investigate the efficacy of Gardenia jasminoides on insulin resistance induced by Non-alcoholic fatty liver disease (NAFLD). 8-week-old C57BL/6 male mice were divided into three groups: control group (Ctrl), high-fat diet group (HFF), and high fat diet with Gardenia jasminoides extract administration group (GJT). Each 10 mice was allocated to each group (a total of 30 mice). All mice were allowed to eat fat-rich diet freely throughout the experiment. To examine the effect of Gardenia jasminoides, we observed weight changes, lipid blot distributions, PPAR-${γ}$, p-IkB, p-JNK in liver tissue, total cholesterol, and glucose levels in serum. Comparing of body weight measurements between 3 groups, in the GJT group, weight gain was significantly suppressed compared to the HFF group. The distribution of lipid blots and positive reaction of PPAR-${γ}$ were significantly lower in GJT group. The expression levels of p-$IκB$ and p-JNK that plays critical roles in the development of insulin resistance were significantly decreased by GJ treatment. Total cholesterol and glucose levels in serum were also significantly lower in GJT group. Gardenia jasminoides has the effect of improving non - alcoholic fatty liver induced insulin resistance through the regulation of lipid metabolism.